(untitled) (Fiep Bulletin - online, 2014)
With the progress of decentralization of the health sector in Brazil in the decade of 1990, the municipal sphere, gradually, became responsible for managing the network of health services, among them the Epidemiological Monitoring. In our daily life of advice along to municipalities in the region of Trairí of V Regional Public Health Unit (V URSAP) of the State of Rio Grande do Norte, found shortcomings in the routine in some Nuclei for the Epidemiological Monitoring (NVE). This study aimed to identify the structure of nuclei and the actions of municipal epidemiological surveillance developed in the V URSAP. This is a descriptive study conducted with 10 coordinators of NVE’s V URSAP in the region of Trairí / RN. The data were obtained through a form of structured interview, in September 2007, following approval of the Committee on Ethics in Research / UFRN and analyzed Epi-Info 3.4. In all the 10 NVE did not exist own room, 70% were without complete multi professional team. Items transport (70%) and equipment (80%) were adequate in most cores analyzed. However, we find that 90% of NVE were with inadequate structure for the development of the shares of VE. As the actions of VE, which identified the activities relating to the collection and processing of data is performed by 100% of NVE, while the analysis, interpretation of data and recommendations for measures of control were present in 80% of nuclei. However, the activities of promotion of the shares of control (80%), evaluation of the efficiency and effectiveness of the measures taken (90%) and dissemination of relevant information (90%) were absent in most nuclei. Accordingly, we believe that the NVE analyzed have mostly inadequacy about their structure and development of actions of VE and needs to be urgently reviewed these aspects managers municipal health of NVE studied.